Distribute elite maize germplasm with high yield potential, and disease resistance to partners - CGIAR Research Program on Maize (2018)
These trials were evaluated in the various countries and several field books have been received from partners for running comprehensive statistical analyses. The results of these analyses will be used to write a report that will be shared with partners to help them select high yielding and stress resilient maize varieties and hybrids for further testing in national performance and participatory on-farm trials.